Profile of drug administration errors in anesthesia among anesthesiologists from Santa Catarina - Erdmann,Thomas Rolf (2016)
INTRODUCTION: Anesthesiology is the only medical specialty that prescribes, dilutes, and administers drugs without conferral by another professional. Adding to the high frequency of drug administration, a propitious scenario to errors is created. OBJECTIVE: Access the prevalence of drug administration errors during anesthesia among anesthesiologists from Santa Catarina, the circumstances in which they occurred, and possible associated factors. MATERIALS AND METHODS: An electronic questionnaire was sent to all anesthesiologists from Sociedade de Anestesiologia do Estado de Santa Catarina, with direct or multiple choice questions on responder demographics and anesthesia practice profile; prevalence of errors, type and consequence of error; and factors that may have contributed to the errors. RESULTS: Of the respondents, 91.8% reported they had committed administration errors, adding the total error of 274 and mean of 4.7 (6.9) errors per respondent. The most common error was replacement (68.4%), followed by dose error (49.1%), and omission (35%). Only 7% of respondents reported neuraxial administration error. Regarding circumstances of errors, they mainly occurred in the morning (32.7%), in anesthesia maintenance (49%), with 47.8% without harm to the patient and 1.75% with the highest morbidity and irreversible damage, and 87.3% of cases with immediate identification. As for possible contributing factors, the most frequent were distraction and fatigue (64.9%) and misreading of labels, ampoules, or syringes (54.4%). CONCLUSION: Most respondents committed more than one error in anesthesia administration, mainly justified as a distraction or fatigue, and of low gravity.